2021
DOI: 10.1177/11779322211021430
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of Phytochemicals on Interleukin-6-Mediated T-Cell Reduction in COVID-19 Patients: A Computational Approach

Abstract: Background: A recent COVID-19 pandemic has resulted in a large death toll rate globally and even no cure or vaccine has been successfully employed to combat this disease. Patients have been reported with multi-organ dysfunction along with acute respiratory distress syndrome which implies a critical situation for patients and made them difficult to breathe and survive. Moreover, pathology of COVID-19 is also related to cytokine storm which indicates the elevated levels of interleukin (IL)-1, IL-6, IL-12, and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
2
7
1
Order By: Relevance
“…The results of this study have better results than the research [26], where the best binding energy value obtained is-5.3 kcal/mol. Nevertheless, it exceeds the research [27] ∆G is-7.7 kcal/mol. In other research [28] ∆G is-7.3 kcal/mol.…”
Section: Discussioncontrasting
confidence: 57%
“…The results of this study have better results than the research [26], where the best binding energy value obtained is-5.3 kcal/mol. Nevertheless, it exceeds the research [27] ∆G is-7.7 kcal/mol. In other research [28] ∆G is-7.3 kcal/mol.…”
Section: Discussioncontrasting
confidence: 57%
“…Many phytocompounds have been used in traditional medicine to treat ailments possibly caused by viruses [62][63][64]. Several studies evaluated the pharmacological nature of the phytocompounds and COVID-19 proteins [65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…Isoorientin, a flavone C-glycoside, showed better binding affinity on IL-6, if compared to all other phytocompounds with a binding energy of −7.7 kcal/mol. Isoorientin with IL-6 interactive residues in molecular interactions were as follow: SER: 91, THR: 92, LEU: 95, PHE: 98, LEU: 140, PHE: 143, LYS: 144, LEU: 147 [ 76 ]. In addition, Prathap et al revealed that stachydrine, a pyrrolidine betaine, binds IL-6 and inhibits it, with a binding energy of −5.9 kcal/mol and hydrogen bonding with GLU: 42 [ 77 ].…”
Section: Discussionmentioning
confidence: 99%